Towards an Ecology of Practices in Academic Filmmaking - Laura Dávila Argoty; Valentina Giraldo Sánchez (Akademisk Kvarter, 2024)
This video-essay proposes to depart from the experimental cinema made by Latin American women in order to highlight the tendencies of this minor cinema in which we can find ecological and formal concerns that cross our geopolitical and imaginary territories. Thus, we aim to identify an ecology of practices within the work of three contemporary filmmakers that despite their distinct styles and approaches, share commonalities and divergences that offer insight into the rich diversity in the same ecosystem. This was done through a montage of material from three short films: 13 Ways of Looking at a Blackbird (2020) by Ana Vaz, Erial (2021) by Javiera Cisterna and Celaje (2020) by Sofia Gallisá Muriente. Through this video essay, we aim to interweave ideas, images, and methodologies towards a cohesive understanding of an ecology of practices in both film and academia. Our aspiration is to foster reflection on academic film practice as a possibility to reveal other means for political, epistemological and aesthetic inquiry.